ENHANCING TEACHERS' ABILITY TO DEVELOP HOTS-BASED ASSESSMENT INSTRUMENTS IN THE MERDEKA CURRICULUM AT ELEMENTARY SCHOOLS - Nirmala, Sri Dewi; Ramdhani, Sendi; Sapriati, Amalia; Puspitasari, Kristanti Ambar; Rumanta, Maman; Marisa, Riandi; Julaeha, Siti; Artanti, Yuli; Hartiningsih, Hartiningsih; Lestari, Puji (LPPM Univ. Ibn Khaldun Bogor, 2024)
Assessment is a critical subsystem in the overall learning process. However, teachers still face challenges in developing assessments, particularly those that align with Higher Order Thinking Skills (HOTS). The results of a needs analysis indicated that teachers at the partner schools require urgent training and guidance in creating both formative and summative assessment instruments. The Community Service Program (PkM) was conducted at SD Negeri Marga Mulya VI, Bekasi City. The PkM activities were based on the Asset-Based Community Development (ABCD) approach and consisted of six stages. The outcomes of this PkM activity include: (1) the successful implementation of training and assistance in the development of assessment instruments, enabling teachers to understand and create assessment tools; (2) the creation of assessment instruments by teachers, which can now be utilized in the learning process; and (3) positive responses from teachers, who reported that the PkM activities significantly benefited them in preparing and applying assessments in teaching. The outcomes of this PkM initiative can be further followed up through discussions and dissemination within the school's Learning Community to deepen understanding.